Left atrial function may mitigate the effect of mitral regurgitation on right chambers in patients with severe aortic valve stenosis. (3rd October 2022) - Urbani, G; Springhetti, P; Quer, L; Dotto, A; Ciceri, L; Fanti, D; Maffeis, C; Tafciu, E; Bergamini, C; Nistri, S; Inciardi, R M; Ribichini, F L; et al.
Abstract: Introduction: Left atrial (LA) function has been associated to right chambers hemodynamics in the context of mitral valve regurgitation (MR). However, this physiological interplay between left atrial function, mitral regurgitation and right ventricular (RV) parameters has not yet been clarified in patients with aortic valve stenosis (AS). Aim of the study: To assess the combination of LA function and different MR grades with right chambers performance and pulmonary non-invasive hemodynamics status in patients with severe AS using an advanced automated echocardiographic approach. Methods: Consecutive patients with severe AS referred to our institution were analyzed. Mitral regurgitation was classified according to integrative guideline-based criteria. 2D advanced speckle tracking echocardiography analysis was conducted to measure the LA peak atrial longitudinal strain (PALS) and right ventricular free wall strain, (RVFWS) using Tomtec Arena, version TTA2 41.00, with dedicated LV/LA/RV analysis option (Tomtec, Unterschlei heim, Germany). All conventional right chambers performance indexes were also measured: TAPSE, S'- TDI, fractional area change, systolic pulmonary artery pressure (sPAP). We featured 3 patients groups based on MR grade and LA function: (a) no/mild MR and preserved PALS (above the median); (c) >mild MR and reduced PALS; (b) the remaining patients with >mild MR and low PALS or >mild MR and high PALS. Results: A total of 102 patients with severe aortic stenosis formed the study cohort: age was 82±9, 47% were female, mean left-ventricular-ejection-fraction 56%±12, more than mild MR was present in 24% of patients, mean PALS was 19±10%, sPAP 38±12 mmHg, RVFW strain 21±6%, and RVFW/sPAP 0.62±0.25. The 3 subgroups presented similar age and sex distribution. Right ventricular function significantly worsened moving from group (a) to (c); RVFW strain decreased from 25±5 (a) to 19±7 (b) and 17±5% (c), p<0.001; sPAP increased from 34±9 (a) to 39±12 (b) and 47±13 mmhg (c), p<0.001; and RVFW/sPAP decreased from 0.76±0.21 (a) to 0.54±0.23 (b) and 0.39±0.11 (c), p<0.001. Patients in the group (c) were more symptomatic (NYHA class III/IV increase from 40% in group a and 63% in group (b) to 80% in group c, p=0.006). When added to MR grade, in a logistic regression analysis, PALS provided incremental prediction of all right ventricular parameters (p<0.01). Conclusion: This study highlights that the combination of MR and reduced LA function is associated with symptoms and RV impairment in patients with severe AS. These preliminary results suggest that preserved LA function may modulate the adverse effects of the AS-MR combination by preventing/delaying the development of pulmonary hypertension and right ventricular dysfunction. Funding Acknowledgement: Type of funding sources: None.